Exploration of Factors Influencing Early Marriage in Adolescents: A Literature Review - Khairunnisa, Cahyaning Auliya; Sitorus, Sarah Angelique Mutiaraku; Puspita, Vidya Diah; Maryati, Ida (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
A phenomenon that often occurs in lower middle economic circles is early marriage. Early marriage can threaten the health and well-being of the couples involved. Not only does it affect health aspects, but it also impacts psychological, social and spiritual aspects. Mental instability in running a household can lead to divorce and domestic violence. This research aimed to explore which factors play a major role in early marriage, especially among adolescents. Using a systematic literature review with keyword “Teenagers AND early marriage AND Factor Influencing” which had a limit criteria of 2019-2024, using English and Indonesian Language, qualitative research design, and full txt. There were 2079 articles SAGE, Portal Garuda, Neliti, and Google Scholar databases and were re-screnned to obtain a total of 7 journals based on inclusion and exclusion criteria with PRISMA Flow 2020 guidelines.  Early marriage is caused by external and internal factors. External factors include socio-economic factors, cultural norms, low level of education, poor parenting while internal factors include love, the desire to be accepted in society life, and new opportunities in life.